Examining suicide assessment measures for research use: Using item response theory to optimize psychometric assessment for research on suicidal ideation in major depressive disorder. Issue 6 (8th July 2021) - McCall, William V.; Porter, Ben; Pate, Ashley R.; Bolstad, Courtney J.; Drapeau, Christopher W.; Krystal, Andrew D.; Benca, Ruth M.; Rumble, Meredith E.; Nadorff, Michael R.
Abstract: Introduction: Progress reducing suicide death will require randomized clinical trials (RCTs) specifically targeting suicide risk. Even large RCTs may not stipulate suicide death as the primary outcome, as suicide death is relatively uncommon. Therefore, RCTs may need to specify suicidal ideation as a proxy indicator of risk. There is no consensus on the best tool for measuring suicidal ideation within RCTs. We contrasted the psychometric performance of three suicidal ideation measures to address this need. Methods: We applied item response theory to the Beck Scale for Suicide Ideation (BSSI), the Columbia‐Suicide Severity Rating Scale (C‐SSRS), and the suicide item of the Hamilton Rating Scale for Depression (HRSD) for 101 outpatients with depression and suicidal ideation participating in a RCT with suicidal ideation as the primary outcome. Results: All measures of suicidal ideation were equally able to detect low and very high levels of suicidal ideation. Conclusions: The choice of the specific measure of suicidal ideation in a clinical trial may be dictated by time and financial resources versus the need for granularity in the interpretation of the scores.